Wilderness Therapy for Abused Women - McBride, Dawn Lorraine; Korell, Gabrielle (Canadian Journal of Counselling and Psychotherapy, 2007)
This paper describes a wilderness weekend retreat for abused women facilitated by the authors. An overview of wilderness therapy, addressing its historical roots, key theoretical perspectives, as well as issues of emotional and physical safety, is presented. Special emphasis is placed on how to create a wilderness experience that is empowering to these women and helps them deal with the challenge of leaving their partner and children for a weekend. Facilitation issues are also addressed and recommendations to enhance the delivery of programs of this nature are given.